Survei Kelompok Usia Terhadap Perilaku Agresivitas Suporter Sepakbola PSIS Semarang - Akhmad Adrian Maulana; Mugiyo Hartono; Bambang Priyono; Dwi Gansar Santi Wijayanti (Indonesian Journal for Physical Education and Sport, 2024)
The purpose of this study was to determine the level of aggressiveness of PSIS Semarang football fans in the adolescent age group, early adulthood, and middle adulthood. This research is included in quantitative research using survey methods. The subject of this study was the Semarang PSIS supporter group. The sampling technique uses purposive sampling while the data collection technique uses questionnaires that have been tested both in validity and reliability. The results showed that the aggressiveness of PSISSemarang football fans in the adolescent age group was in the medium category of 37.23%, the early adult age group was in the medium category of 35.38%, the middle adult age group was in the medium category of 40.28% and the PSIS Semarang fan group had a medium aggressiveness level of 33.21%. The conclusion in this study is that the level of aggressiveness of PSIS Semarang supporters in the adolescent, early adult and middle adult age groups is in the medium category.